2018
DOI: 10.1103/physrevlett.120.167701
|View full text |Cite
|
Sign up to set email alerts
|

Linear Hyperfine Tuning of Donor Spins in Silicon Using Hydrostatic Strain

Abstract: We experimentally study the coupling of group V donor spins in silicon to mechanical strain, and measure strain-induced frequency shifts that are linear in strain, in contrast to the quadratic dependence predicted by the valley repopulation model (VRM), and therefore orders of magnitude greater than that predicted by the VRM for small strains |ϵ|<10^{-5}. Through both tight-binding and first principles calculations we find that these shifts arise from a linear tuning of the donor hyperfine interaction term by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 67 publications
4
57
0
Order By: Relevance
“…The calculations were done with the sp 3 d 5 s * model [44], in supercells with side L = 48a = 26 nm. On-site corrections were included on the impurity atom [45]. We can see thatρ at the end of the previous section), and this confirms that it may be neglected for the purpose of studying the excited states.…”
Section: Quadratic Zeeman Effectmentioning
confidence: 64%
“…The calculations were done with the sp 3 d 5 s * model [44], in supercells with side L = 48a = 26 nm. On-site corrections were included on the impurity atom [45]. We can see thatρ at the end of the previous section), and this confirms that it may be neglected for the purpose of studying the excited states.…”
Section: Quadratic Zeeman Effectmentioning
confidence: 64%
“…22. In our devices, bismuth donor spins experience large strain when cooled to low temperature because of the differential thermal expansion of Al and Si 18,23 , which leads to ESR lines much broader than both κ and the Rabi frequency 2gα in our experiments. We model this by a constant distribution ρ δ .…”
Section: Methodsmentioning
confidence: 83%
“…Applying strain to a valley shifts its energy relative to the conduction band minimum, resulting in a rearrangement of the relative populations of each valley which can be described as a mixing of the donor A 1 and E states. The degree of mixing can be calculated using the "valley repopulation" model (VRM) [47], which predicts a quadratic shift of the hyperfine interaction with an applied strain [48]: The second-order model predicts shifts an order of magnitude larger than the VRM does, as well as displays bipolar frequencies due to its strong linear dependence.…”
Section: Hyperfine Interactionmentioning
confidence: 99%
“…Very recently, it was found that the hyperfine interaction of donors in silicon is also sensitive to the hydrostatic component of strain [48]. This result is surprising, as the VRM predicts no hyperfine reduction for strains that shift all of the valleys by the same energy.…”
Section: Hyperfine Interactionmentioning
confidence: 99%